Evolution of B cell analysis and Env trimer redesign - Karlsson Hedestam, Gunilla B (Immunol Rev, 2017)
HIV-1 and its surface envelope glycoproteins (Env), gp120 and gp41, have evolved immune evasion strategies that render the elicitation of effective antibody responses to the functional Env entry unit extremely difficult. HIV-1 establishes chronic infection and stimulates vigorous immune responses in the human host; forcing selection of viral variants that escape cellular and antibody (Ab)-mediated immune pressure, yet possess contemporary fitness. Successful survival of fit variants through the gauntlet of the human immune system make this virus and these glycoproteins a formidable challenge to target by vaccination, requiring a systematic approach to Env mimetic immunogen design and evaluation of elicited responses. Here, we review key aspects of HIV-1 Env immunogenicity and immunogen re-design, based on experimental data generated by us and others over the past decade or more. We further provide rationale and details regarding the use of newly evolving tools to analyze B cell responses, including approaches to use Next Generation Sequencing for antibody lineage tracing and B cell fate mapping. Together, these developments offer opportunities to address long-standing questions about the establishment of effective B cell immunity elicited by vaccination, not just against HIV-1.